2018
DOI: 10.12659/msm.910294
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidin Inhibits Anti-Apoptotic Bcl-2 Family Proteins and Induces Apoptosis in Human Osteosarcoma Cell Lines MG-63 and MNNG/HOS via Mitochondria-Dependent Pathway

Abstract: BackgroundCantharidin (CTD) is one of the major active ingredients of blister beetles and has significant antitumor activity in many cancer cell lines. The aim of our study was to evaluate the effect of CTD on the apoptosis of human osteosarcoma cells MG-63 and MNNG/HOS, and to explore the possible molecular mechanism.Material/MethodsOsteosarcoma cells MG-63 and MNNG/HOS were treated with varying concentrations of CTD. The proliferation inhibition of cells was detected by MTS. Flow cytometry and Hoechst 33258 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Liu et al reported that dysregulation of the ezrin/NF-κB signal pathway can activate epithelial-mesenchymal transition (EMT) in osteosarcoma, thus contributing to cancer progression and metastasis [25]. Designing the drugs or treatment methods specific to the genetic mutations in tumorigenesis may provide novel therapeutic methods for osteosarcoma [26]. Recently, a variety of molecular markers and therapeutic targets have been confirmed for osteosarcoma, including miRNAs, lncRNAs, and some specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that dysregulation of the ezrin/NF-κB signal pathway can activate epithelial-mesenchymal transition (EMT) in osteosarcoma, thus contributing to cancer progression and metastasis [25]. Designing the drugs or treatment methods specific to the genetic mutations in tumorigenesis may provide novel therapeutic methods for osteosarcoma [26]. Recently, a variety of molecular markers and therapeutic targets have been confirmed for osteosarcoma, including miRNAs, lncRNAs, and some specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions that disrupt intracellular balance, such as mitochondrial dysfunction, calcium imbalance, and DNA mutation, can activate the intrinsic apoptotic pathway, which is mainly composed of and regulated by members of the multidomain B cell lymphoma 2 (Bcl-2) family (Shukla et al, 2017;Jin et al, 2018). This family includes the antiapoptotic molecules Bcl-2 and Bcl-XL (Perciavalle et al, 2012;Wen-Juan et al, 2012;Feng et al, 2018) and the proapoptotic molecules Bcl-2-related X protein (Bax) and BCL-2 antagonist (Bak) (Hsu et al, 1997;Mathai et al, 2005), among others. The intrinsic pathway is activated mainly by the interaction of Bcl-2-like protein 11 (BCL2L11, also known as Bim) or BH3-interacting domain death agonist (Bid) with Bax or Bak.…”
Section: Apoptotic Mechanismmentioning
confidence: 99%
“…Overexpression and mutations in the BCL2 gene are correlated with cancer development, and BCL2 upregulation has been reported in several types of cancers [65][66][67]. Furthermore, the correlation between BCL2 inhibition and apoptosis inducement has been reported by various studies [68][69][70]. The combination of MTX and Que down-regulated BCL2 significantly, accelerating apoptosis inducement.…”
Section: Discussionmentioning
confidence: 93%